Diagnóstico y diseño del sistema de alumbrado público de la vía Intervalles, del tramo El Tambo – La Capilla del cantón Catamayo - Merino González, Carlos Alberto (2025)
The purpose of this curricular integration work is to develop the diagnosis and design of the lighting system through the implementation of LED technology in the public road from El Tambo-La Capilla sector, located in the Catamayo canton, province of Loja, with an extention that covers 4.4 km. The study includes a diagnosis of the current state of the existing lighting network to determine possible deficiencies, which serves as a starting point for the design of the public lighting network. Ulysse “3.5.9” software is used to simulate the design and verify compliance with the applicable lighting standards, thus ensuring compliance with the relevant regulations. The methodology carried out allowed for an exhaustive analysis of the current state of public lighting, in order to determine the existing lighting areas, as well as the distribution points present. This information serves as the basis for the design of the public lighting network using LED lighting, which complies with the photometric standards CIE 115 - 1995 and CIE 140 - 2000 established by the lighting and design regulations, including the RETILAP, EERSSA, MERNNR and ARCERNNNR regulations. The current system of the existing network consists of 8 distribution points strategically identified for the possible expansion of the proposed network. Of these, only two points are currently equipped with sodium vapor luminaires, which do not comply with current lighting and design standards. The necessary information has been gathered to develop the design of the projected street lighting network, ensuring compliance with the regulations established in this study. A public lighting network equipped with LED luminaires, which meet the technical lighting requirements, has been chosen to improve lighting conditions in critical sectors. The validity of this design has been verified by simulations, demonstrating that the photometric parameters meet the required standards for the corresponding lighting class. Finally, the design of the projected street lighting network with LED technology would result in a significant improvement in both quality and energy efficiency, contributing to community development by enhancing the safety of residents and tourists traveling through the area. Keywords: LED, public lighting network, lighting regulations, Ulysse, energy efficiency.